Utilizing a health information exchange to facilitate COVID-19 VA primary care follow-up for Veterans diagnosed in the community. Issue 1 (16th March 2021) - Sherman, Rachel L; Judon, Kimberly M; Koufacos, Nicholas S; Guerrero Aquino, Vivian M; Raphael, Shaniqua M; Hollander, Judith T; Boockvar, Kenneth S
Abstract: The use of alerts from the Bronx RHIO, a health information exchange (HIE) to identify James J. Peters VAMC patients diagnosed with COVID-19 in the community was described to facilitate COVID-19 VA primary care follow-up. COVID-19 hospitalization and testing alerts were delivered on a Bronx RHIO facility report. VA COVID-19 follow-up care by telephone and video was guided by local COVID-19 clinical pathways, electronic health record (EHR) templates, and tracking through a database. VA received 180 RHIO alerts for 111 unique patients, and 88 had positive non-VA testing from March to June 2020. 41% of the 88 had non-VA admissions and 23% died. 63% received VA primary care follow-up of COVID-19 symptoms documented by custom EHR templates. The HIE identified 11% of the facility COVID-19 patients. HIE alerts can be used to identify facility COVID-19 patients diagnosed in the community and facilitate follow-up by their VA primary care teams.